Relationships between Body Mass Index, Psychological Stress, Physical Activity, and Oligomenorrhea in Adolescents at Yasinat Islamic Boarding School, Surabaya - Rosida, Silvi Dina; Sa'adi, Ashon; Purwanto, Bambang (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Oligomenorrhea is one of the most common types of menstrual cycle disorders. Cases have increased in recent decades. Women with oligomenorrhea have menstrual intervals of more than 35 days and less than 90 days. Oligomenorrhea is common in adolescents, particularly 75% of women in late adolescence suffer from oligomenorrhea. The study aims to analyze the effect of BMI, psychological stress, and physical activity on the incidence of oligomenorrhea in young women in Yasinat Islamic Boarding School. Subjects and Method: This was an analytical observational study with a cross-sectional design. The study sample was adolescents aged 17-19 years with a total of 82 students at Yasinat Islamic Boarding School. The dependent variable was oligomenorrhea. Independent variables were BMI, stress psychology, and physical activity. The study instrument was a questionnaire. The study data were analyzed using the Chi-Square. Results: BMI <18.5 kg/m2 and BMI >25 kg/m2 or 24.4% experienced oligomenorrhea, 3.7% of subjects with light activity experienced oligomenorrhea, while subjects with physical activity of more than 40% experienced oligomenorrhea, 21.7 % of subjects with the normal category experienced oligomenorrhea, 27.8% mild stress, 47.1% moderate stress experienced oligomenorrhea. BMI had a significant effect on oligomenorrhea (p= 0.006). Psychological stress (p= 0.227) and physical activity (p= 0.224) showed no significant influence on oligomenorrhea. Conclusion: There is a relationship between BMI and oligomenorrhea incidence. However, there is no relationship between psychological stress, physical activity, and oligomenorrhea. Keywords: physical activity, body mass index, oligomenorrhea, psychological stress. Correspondence: Silvi Dina. Study Program of Midwifery, Faculty of Medicine, Universitas Airlangga. Jl. Mayjen Pro. Dr. Moestopo No. 47, Surabaya 60132, East Java, Indonesia. Email: silvi.dina.rosida-2019@fk.unair.ac.id. Mobile: +6282140485431.